Mispronunciation of vowels and tones in hausa disyllabic words by yoruba native speakers - Maikanti, Sale (2021)
Hausa and Yorùbá are two different African languages with different sets of vowels, even though they share some common vowels, including tones. The phonemic distinction between the five (long) vowels, in addition to the two diphthongs of Hausa, seems to cause learning difficulties among the Yorùbá native speakers learning Hausa as a second language. Such challenge tends to cause substitution of vowels and tones in the first and second syllables when pronouncing disyllabic Hausa words by the Yorùbá speakers. This study aimed to address the following research questions: (i) Does a significant difference exist between the performance of elementary and advanced Yorùbá native speaker learners in the pronunciation of Hausa vowels and tones?; (ii) What are the Hausa vowels that were substituted in the first and second syllables by elementary and advanced Yorùbá native speaker learners of Hausa?; and (iii) What are the Hausa tones that were substituted in the first and second syllables by elementary and advanced Yorùbá native speaker learners of Hausa? Eighty-eight Yorùbá native speakers in elementary and advanced levels who were 18-years-old and above were recruited as participants using purposive sampling. The data was collected from the participants using different stimuli in carrier phrases, which were audio-recorded and transcribed for quantitative and qualitative analysis to provide insights into the study. Errors identified in the study were categorised based on patterns, and were explained within the framework of two theories: ‘Error Analysis Model’ by Corder (1967) and ‘Revised Speech Learning Model’ by Flege and Bohn (2020). The results of the elementary and advanced participants revealed that there was a significant difference in the pronunciation of vowels and tones in the first and second syllables. Generally, the advanced participants showed a significantly lower error rate in the pronunciation of Hausa vowels and tones compared with elementary participants. The research also discovered how Yorùbá native speaker learners of Hausa mispronounce some disyllabic Hausa words due to substitution. The study further identified a number of vowels and tones that were substituted, and the vowels they were substituted with, in the first and second syllables. The most frequent vowel substitutions across the elementary and advanced levels in the first and second syllables include /o/ → [o:], /a/ → [a:], and /u/ → [u:]. While the frequent tone substitutions across the two groups in the first syllable were from high to low, falling to high, and falling to low tones. In the second syllable, tones were substituted from low to high, high to low, and falling to high. To address mispronunciation problems among the Yorùbá native speakers, teachers of Hausa as a second language should focus more on the problematic sounds (vowels and tones), especially when teaching the elementary participants. Yorùbá native speakers learning Hausa should also be encouraged to learn how to produce the less difficult Hausa vowels and tones first, followed by the difficult ones in pronunciation both within and outside the classroom through regular practice. The study will assist the learners of Hausa as a second language to understand how to read, write, and speak fluently in Hausa. It will also add to the body of existing literature, particularly on Hausa L2 phonetics and phonology. The research serves as a guide for the Hausa language curriculum development in redesigning a new school curriculum focusing on correct pronunciation. Combining Corder’s (1967) ‘Error Analysis Model’ and Flege and Bohn’s (2020) ‘Revised Speech Learning Model’ which guided the present study and reflects the novelty of this study.